Phylogenetic analysis of the partial sequences of the env and tax BLV genes reveals the presence of genotypes 1 and 3 in dairy herds of Antioquia, Colombia (2023)
ABSTRACT: Bovine leukemia virus (BLV) is a retrovirus that primarily infects dairy cows. Although few studies have also used the tax gene, phylogenetic studies of BLV use mostly the env gene. The aim of this work was to establish the circulating genotypes of BLV in specialized dairy cattle from Antioquia, Colombia. Twenty blood samples from Holstein Friesian cows were collected, and their DNA was isolated. A PCR was performed for a partial region of the env and tax genes. A phylogenetic analysis was carried out using the maximum likelihood and Bayesian methods for both genes. Nineteen sequences were identified as genotype 1 by env and tax genes. Only one sequence was clustered with genotype 3 and had the highest proportion of different nucleotide sites compared to other strains. Four amino acid substitutions in the 134 amino acid residue fragment of the Env protein were identified in the Colombian sequences, and three new amino acid substitutions were reported in the 296 amino acid residue fragment of the Tax protein. R43K (Z finger), A185T (Activation domain), and L105F changes were identified in the genotype 3 sample. This genotype has been reported in the United States, Japan, Korea, and Mexico, but so far, not in Colombia. The country has a high rate of imported live animals, semen, and embryos, especially from the United States. Although it is necessary to evaluate samples from other regions of the country, the current results indicate the presence of two BLV genotypes in specialized dairy herds.